Is more information always better? : the effect of information on the validity of contingent valuations - Müller, B (Oxford Institute for Energy Studies, 1997)
Within the framework of consumer’s surplus, a theory of Contingent Valuation (CV) is introduced which accommodates a cost-parameter for the good or policy to be valued. This theory is then used to discuss the validity of value estimates established by means of CV-instruments with different (cost-) information. Against the prevailing view that such instruments must contain a description of how the good to be valued is meant to be generated and how this generation is to be financed, it is argued that, if the aim of the valuation is to establish compensatory damages, then the ‘safest’ instrument (i.e. the least likely to be biased) is the one where the good is said to be provided for free, without any further information about means of generation or payment vehicle. Indeed, it is shown that the inclusion of such further information opens up the possibility of an array of different biases which would invalidate the estimates for the purpose of establishing compensatory damages. Although there is no theoretically predictable direction for these biases, the mere fact that they may exist does put a question mark on the compensatory damage figures which have been estimated according to the current practice of CV.